The Implementation of Merdeka Belajar Policy in East Java - Ahid, Nur; Sufirmansyah, Sufirmansyah (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
This article presents an investigation into the planning, implementation, challenges and solutions of the Merdeka belajar policy in East Java. The research is based on fieldwork conducted using a qualitative case study approach. The data were collected through interviews, observations, and document analysis, and subsequently analysed using the interactive technique proposed by Miles and Huberman. The planning process comprised two distinct activities: firstly, the socialisation of the four pillars of the Merdeka Belajar policy by the Ministry of Education and Culture, and secondly, the preparation of the necessary infrastructure, including the Dapodik database and e-learning systems. The implementation process was conducted in three phases: firstly, the optimisation of Ministry guidelines; secondly, participation in the Motivating School programme; and thirdly, enhancement of student-centred online learning. The implementation of the Merdeka Belajar policy encountered several challenges, including discrepancies in the understanding of the policy among teachers and delays in the introduction of online learning due to the diverse socio-economic backgrounds of students and the varying levels of readiness of educational institutions. In order to address these issues, two solutions were implemented. The first of these was to strengthen teachers' comprehension through workshops and outreach, while the second was to incorporate limited face-to-face learning while progressing towards blended learning.